IL-33 Drives Expansion of Type 2 Innate Lymphoid Cells and Regulatory T Cells and Protects Mice From Severe, Acute Colitis - Ngo Thi Phuong, Nhi; Palmieri, Vittoria; Adamczyk, Alexandra; Klopfleisch, Robert; Langhorst, Jost; Hansen, Wiebke; Westendorf, Astrid M.; Pastille, Eva (Frontiers in Immunology, 2021)
The hallmarks of inflammatory bowel disease are mucosal damage and ulceration, which are known to be high-risk conditions for the development of colorectal cancer. Recently, interleukin (IL)-33 and its receptor ST2 have emerged as critical modulators in inflammatory disorders. Even though several studies highlight the IL-33/ST2 pathway as a key factor in colitis, a detailed mode of action remains elusive. Therefore, we investigated the role of IL-33 during intestinal inflammation and its potential as a novel therapeutic target in colitis. Interestingly, the expression of IL-33, but not its receptor ST2, was significantly increased in biopsies from the inflamed colon of IBD patients compared to non-inflamed colonic tissue. Accordingly, in a mouse model of Dextran Sulfate Sodium (DSS) induced colitis, the secretion of IL-33 significantly accelerated in the colon. Induction of DSS colitis in ST2-/- mice displayed an aggravated colon pathology, which suggested a favorable role of the IL 33/ST2 pathway during colitis. Indeed, injecting rmIL-33 into mice suffering from acute DSS colitis, strongly abrogated epithelial damage, pro-inflammatory cytokine secretion, and loss of barrier integrity, while it induced a strong increase of Th2 associated cytokines (IL-13/IL-5) in the colon. This effect was accompanied by the accumulation of regulatory T cells (Tregs) and type 2 innate lymphoid cells (ILC2s) in the colon. Depletion of Foxp3+ Tregs during IL-33 treatment in DSS colitis ameliorated the positive effect on the intestinal pathology. Finally, IL-33 expanded ILC2s, which were adoptively transferred to DSS treated mice, significantly reduced colonic inflammation compared to DSS control mice. In summary, our results emphasize that the IL-33/ST2 pathway plays a crucial protective role in colitis by modulating ILC2 and Treg numbers.